Global marketing : foreign entry, local marketing, and global management - Johansson, Johny K. (Chicago : Irwin, 1997)
This book is divided into four parts: Fundamentals; Foreigh entry; Local marketing; and Global management.
Keywords: Management; Export marketing; Export marketing -- Management; Export marketing